Numerical study of turbulence structures affected by body forces in a turbulent boundary layer - Abhilash Paul (2012)
Even though it is understood that introduction of spanwise wall oscillation into a turbulent boundary flow is a promising technology in reducing the skin friction drag, the physical mechanism behind this phenomenon is not fully explored. This study is an attempt to understand the mechanism of the drag reduction in such a flow.